Experimental Approaches to Studying Cumulative Cultural Evolution. (June 2016) - Caldwell, Christine A.; Atkinson, Mark; Renner, Elizabeth
In humans, cultural traditions often change in ways that increase efficiency and functionality. This process, widely referred to as cumulative cultural evolution, sees beneficial traits preferentially retained, and it is so pervasive that we may be inclined to take it for granted. However, directional change of this kind appears to distinguish human cultural traditions from behavioral traditions that have been documented in other animals. Cumulative culture is therefore attracting an increasing amount of attention within psychology, and researchers have begun to develop methods of studying this phenomenon under controlled conditions. These studies have now addressed a number of different questions, including which learning mechanisms may be implicated and how the resulting behaviors may be influenced by factors such as population structure. The current article provides a synopsis of some of these studies and highlights some of the unresolved issues in this field.